Notes on Quercus ilex L. in Liguria (NW Italy) - Barberis, G.; Peccenini, S.; Paola, G. (Plant Ecology, 1992)
The climatic characteristics of the Liguria region have been outlined by means of raw data and derived indices (water balance related to potential evapotraspiration, Rivas-Martinez's index of mediterraneity and thermicity, De Martonne's index of dryness, and Emberger's pluviothermic quotient and index of summer dryness). Their interpretation suggests that Liguria is a boundary region between two different climatic areas: the Mediterranean and that of Central Europe. The distribution of Quercus ilex communities in Liguria have suffered the heavy consequences of human activity on the coastal belt of the region. There is, however, sufficient evidence to show that their presence is closely linked to climatic conditions. Quercus ilex communities are absent from the western coastal belt where the annual water balance is below -50 mm and high mean temperatures occur. They are also absent from marly limestone dominated areas where annual water balance is below 300 ram. Quercus ilex woods show a preference for water balance values between 0 and 600, with the better de- veloped forests being found in central and eastern coastal Liguria. The Ligurian Quercus ilex woods are ascribed to Quercetum ilicis Br.-BI. 1915. Given that the pres- ence within their floristic composition of a group of species of Querco-Fagetea (more species in eastern stands, few in western ones) is an almost constant characteristic, the subass, fraxino-ostryetosum Mariotti 1984 can be retained for many of them. Quercus ilex is not present in the initial succession stages of Mediterranean Liguria vegetation. It can be found in later stages when the vegetation is more fully de- veloped towards a maquis type structure. In this case it tends to become dominant and the community develops (if no fire or other human interference occurs) into a Quercus ilex forest. Frequently, this succession takes place under an old tree layer cover (generally Pinus sp.), a remnant of man's past management of the vegetation in the area.
Keywords: Mediterranean climate; quercus ilex communities; quercus ilex ecology